Home in transition : the cultural construction of Heimat - Watzlawik, Meike, 1975- (Advances in cultural psychology., 2023)
"This book presents an integrative perspective on home or Heimat showing that it is much more than the place we were born or where we live. This book brings fresh theoretical and empirical perspectives on what home is and can be from different viewpoints. The chapters invite the reader to face challenging questions of what we learn about Heimat, when it is taken from us, threatened, left on purpose or when we set out on the journey to find one. The chapters are written by psychologists throughout, but are expanded in perspective by comments from the groups of people featured in the chapters, who are thus given their own voice. The book ends with a suggestion how all the different perspectives can be unified in the framework of general model of cultural psychology. "All in all-the reader of this volume gains an access to the most intricate phenomenon of human ways of being-that of home. Impossible to define in terms of the scientific lore of psychology, intuitively understandable in everyday life, and basis for deep desires if the feeling of home is lost." This book will be rewarding reading for professionals and students from cultural psychology, cultural and psychological anthropology, sociology, and related disciplines, asking the question of what home is and how individuals can be supported in finding it"--